2010
DOI: 10.1371/journal.pone.0015402
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin Levels and ANG Genotypes: Dysregulation in Amyotrophic Lateral Sclerosis

Abstract: ObjectiveTo determine whether 5 single nucleotide polymorphisms (SNPs) associate with ALS in 3 different populations. We also assessed the contribution of genotype to angiogenin levels in plasma and CSF.MethodsAllelic association statistics were calculated for polymorphisms in the ANG gene in 859 patients and 1047 controls from Sweden, Ireland and Poland. Plasma, serum and CSF angiogenin levels were quantified and stratified according to genotypes across the ANG gene. The contribution of SNP genotypes to varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…For example, Montero et al reported that serum ANG concentrations were significantly elevated in patients with breast cancer [ 11 ]; however, others did not observe this phenomenon [ 12 – 14 ]. Two of three studies investigating the association between serum ANG levels and amyotrophic lateral sclerosis (ALS) reported that serum ANG levels were elevated in affected patients compared with those in control subjects [ 15 , 16 ]; however, the other study drew the opposite conclusion [ 17 ]. These inconsistent results may be attributable to the limited numbers of subjects, as well as to small differences between the patients and healthy controls enrolled in each study.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Montero et al reported that serum ANG concentrations were significantly elevated in patients with breast cancer [ 11 ]; however, others did not observe this phenomenon [ 12 – 14 ]. Two of three studies investigating the association between serum ANG levels and amyotrophic lateral sclerosis (ALS) reported that serum ANG levels were elevated in affected patients compared with those in control subjects [ 15 , 16 ]; however, the other study drew the opposite conclusion [ 17 ]. These inconsistent results may be attributable to the limited numbers of subjects, as well as to small differences between the patients and healthy controls enrolled in each study.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to its upregulation in various cancers, ANG is downregulated in amyotrophic lateral sclerosis (ALS) (McLaughlin et al, 2010), Parkinson's disease (PD) (Steidinger et al, 2011) and Alzheimer's disease (Kim and Kim, 2012). More importantly, loss-of-function mutations have been found in patients with ALS and PD (Conforti et al, 2008;Gellera et al, 2008;Greenway et al, 2006;Paubel et al, 2008;van Es et al, 2009;Wu et al, 2007).…”
mentioning
confidence: 99%
“…ANG plays important role in number of pathogenic conditions including cancer and neurodegenerative diseases by modulating cell growth and survival properties [2]. In contrast to being up regulated in cancer, ANG is down regulated in neurodegenerative diseases such as amyotrophic lateral sclerosis, Parkinson and Alzheimer disease [3][4][5]. Role of ANG in neurodegenerative diseases have been documented due to function lose mutations found in patients [6,7].…”
Section: Introductionmentioning
confidence: 99%